PENGARUH BRAND IMAGE, PROMOSI, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PIZZA HUT DI MASA PANDEMI COVID-19 - Sarah Luthfiyyah Anjani (2021)
The Covid-19 pandemic has had an impact on the economy in Indonesia. Almost all industrial sectors have been affected by the Covid-19 pandemic, one of which is the accommodation and food and beverage sector. Pizza hut is one of the restaurants affected by Covid-19. This research is a quantitative research that aims to determine the influence of each brand image, promotion, and price on purchasing decisions. The population of this study is the people of West Jakarta who know and consume Pizza Hut during the Covid-19 pandemic. Sources of data obtained through the distribution of questionnaires to 100 respondents using google form. The sampling technique used is non-probability sampling with purposive sampling type. The analytical tool used in this research is SmartPLS 3.0. The results obtained from this study are (1) Brand Image has a positive effect of 0.790 and is significant. (2) Promotion has a positive effect of 0.042 and is not significant. (3) Price has a positive effect of 0.077 and is not significant. With an adjusted R square value of 0.787 or 78.7%.